On the Measurement of Import Substitution - Morley, Samuel A.; Smith, Gordon W. (American Economic Review, 1970)
Most auithors have divided this number by the increase in doniestic production obtain the percenttage of growth in the sector accounted for, due to, or attributable to import substitution.2 Because of its narrow definition of imports, however, Clhenery's original approach misses much of what can be meaningfully considered as import substitution. In this paper we examine the nature of this bias and attempt correct it by expanding our concept of imports include the intermediate demands generated by import substitutioin. We then compare our measure one proposed by Chenery, Shuntaro Shishido, and Tsunehiko Watanabe which included intermediates in a rather different fashion. Finally, we present calculations for Brazil 1949-64 give some idea of the magnitude of the bias of the original Chenery measure for a semi-industrialized LDC. These results, together with a brief examination of import substitution in other countries, suggest that for long periods of industrialization and/or for international cross sections, import substitution measures which do not incorporate intermediate demwands can be very misleading even as descriptive tools.